Thrombocytopenia in neonates and the risk of intraventricular hemorrhage: a retrospective cohort study - Lopriore Enrico; van den Bruele Tjitske; von Lindern Jeannette S; Walther Frans J (BMC, 2011)
Abstract Background The overall prevalence of thrombocytopenia in neonates admitted to neonatal intensive care units ranges from 22 to 35%. There are only a few small studies that outline the relationship between the severity of thrombocytopenia and the risk of bleeding. This makes it difficult to form an evidence-based threshold for platelet transfusions in neonatal patients. The aim of this study was to determine the prevalence of thrombocytopenia in a tertiary neonatal intensive care unit and to study the relation between thrombocytopenia and the risk of intraventricular hemorrhage (IVH). Methods We performed a retrospective cohort study of all patients with thrombocytopenia admitted to our neonatal tertiary care nursery between January 2006 and December 2008. Patients were divided into 4 groups according to the severity of thrombocytopenia: mild (100-149 × 109/L), moderate (50-99 × 109/L), severe (30-49 × 109/L) or very severe (< 30 × 109/L). The primary outcome was IVH ≥ grade 2. Pearson's chi-squared and Fischer's exact tests were used for categorical data. ANOVA, logistic regression analysis and multivariate linear regression were used for comparisons between groups and for confounding factors. Results The prevalence of thrombocytopenia was 27% (422/1569). Risk of IVH ≥ grade 2 was 12% (48/411) in neonates with versus 5% (40/844) in neonates without thrombocytopenia (p < 0.01). After multivariate linear regression analysis, risk of IVH ≥ grade 2 in the subgroups of thrombocytopenic infants was not significantly different (p = 0.3). After logistic regression analysis the difference in mortality rate in neonates with and without thrombocytopenia was not significant (p = 0.4). Similarly, we found no difference in mortality rate in the subgroups of neonates with thrombocytopenia (p = 0.7). Conclusion Although IVH ≥ grade 2 occurs more often in neonates with thrombocytopenia, this relation is independent of the severity of thrombocytopenia. Prospective studies should be conducted to assess the true risk of hemorrhage depending on underlying conditions. Randomized controlled trials are urgently needed to determine a safe lower threshold for platelet transfusions.